Peran Guru Dalam Menekan Dampak Bullying Terhadap Motivasi Belajar Siswa: Penelitian - Sofyan Dea Sanjaya; Novi Nitya Santi; Nurita Primasatya (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Bullying in elementary schools has become a serious issue affecting students’ psychological well-being and academic performance. This study aims to analyze the impact of bullying on students’ learning motivation and the role of teachers in minimizing such effects. The research employed a qualitative approach using a case study at SDN Petungroto. Data were collected through observation, in-depth interviews with teachers and students, and documentation review. The findings revealed three main points: (1) various forms of bullying occurred, including physical, verbal, and social bullying; (2) students who were victims of bullying experienced a significant decrease in intrinsic and extrinsic motivation, indicated by lack of classroom participation and reduced interest in learning; and (3) teachers played a crucial role in handling bullying through monitoring, collaboration with parents, counseling, and character education programs. The study emphasizes the importance of creating a safe school environment and strengthening teacher involvement in anti-bullying strategies to improve students’ learning motivation.